2009
DOI: 10.1093/geronb/gbn011
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Built Environment to Perceived Social Support and Psychological Distress in Hispanic Elders: The Role of "Eyes on the Street"

Abstract: Architectural features that facilitate direct, in-person interactions may be beneficial for Hispanic elders' mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
94
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 76 publications
2
94
1
Order By: Relevance
“…Beyond the immediate home, the characteristics of the surrounding natural and built environments (i.e., places and spaces created or modified by people), can provide important resources and exposures relevant for early child health and development (Dunn, 2012). The physical design and characteristics of the neighborhood environment are well established influences on a range of social and health outcomes among adult populations (Transportation Research Board, 2005;Brown et al, 2009;Pereira et al, 2012;Wood et al, 2008;Green et al, 2003;Ewing et al, 2003). Potential developmentally salient physical characteristics of neighborhoods include access to and the quality of local facilities and services (e.g., recreation centers and libraries), retail (e.g., food outlets), recreational opportunities (e.g., parks and nature), street traffic, public transportation, and the physical quality of child-related care, educational and health care facilities (Center on the Developing Child, 2010; Goldfeld et al, 2015).…”
mentioning
confidence: 99%
“…Beyond the immediate home, the characteristics of the surrounding natural and built environments (i.e., places and spaces created or modified by people), can provide important resources and exposures relevant for early child health and development (Dunn, 2012). The physical design and characteristics of the neighborhood environment are well established influences on a range of social and health outcomes among adult populations (Transportation Research Board, 2005;Brown et al, 2009;Pereira et al, 2012;Wood et al, 2008;Green et al, 2003;Ewing et al, 2003). Potential developmentally salient physical characteristics of neighborhoods include access to and the quality of local facilities and services (e.g., recreation centers and libraries), retail (e.g., food outlets), recreational opportunities (e.g., parks and nature), street traffic, public transportation, and the physical quality of child-related care, educational and health care facilities (Center on the Developing Child, 2010; Goldfeld et al, 2015).…”
mentioning
confidence: 99%
“…Having neighborhood environment of these positive potentials encourages one to invest time, social and physical resources to generate meaningful attachment to the community, and local social support (Boyce, 2006;Mee, 2009). Architectural characteristics of the dwellings (S. Brown, et al, 2009), appropriated outdoor space enclosures A., 2(5) Oct / Dec 2017 (p.39-51) Ghazzeh (1999) found that near home space often serves as a substitute for large open spaces as they contribute little to resident's good neighborhood perception and evaluation. People value opportunities to walk around and sit in small groups near their homes which more effectively lead to friendship formation and maintenance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Having neighborhood environment of these positive potentials encourages one to invest time, social and physical resources to generate meaningful attachment to the community, and local social support (Boyce, 2006;Mee, 2009). Architectural characteristics of the dwellings (S. Brown, et al, 2009), appropriated outdoor space enclosures (Al-Homoud & Tassinary, 2004), and outdoor semi-private spaces (Williams, 2005) also affect social interaction and social support among neighbors. For children, different configurations flats afford different outdoor space appropriation and experiences (Azhan Abdul Aziz & Ahmad, 2010;Azhan Abdul Aziz & Ahmad, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Imported virtual water has also been called "exogenous water" [8]. Measuring virtual water is a useful concept in assessing water resource management as it permits the comparison of crops and livestock from the perspective of embedded water [9]. A number of studies have recognized the usefulness of the concept of virtual water for analyzing production patterns and associated water flows [10].…”
Section: Introductionmentioning
confidence: 99%